Edukasi dan Bimbingan untuk Pencegahan Perilaku Bullying pada Siswa-Siswi SD Surabaya - Lusiani, Etik; Silalahi, Veronica; Wiguna, Yunita (Universitas Baiturrahim, 2025)
Bullying occurs when a person feels oppressed by the behavior of others and fears that bad behavior may occur. Bullying behavior is aggressive behavior, consisting of two namely instrumental aggression, a tool used to achieve aggressive behavior. The types of bullying behavior that occur are sexual violence, physical altercations and bullying. There are reports from students from the results of interviews at SD Surabaya students often mock other friends, call their friends with nicknames such as fat, short and also push their friends on purpose. The purpose of providing information about bullying knowledge and behavior is so that elementary school students in Surabaya are able to recognize, know about bullying behavior properly, and prevent victims of bullying. The process of this activity begins with the principal of an elementary school in Surabaya submitting a request to provide health information to the LPPM unit of St. Vincentius a Paulo Catholic STIKES, then getting permission to carry out community service activities. The results after the health education process were changes in the level of knowledge of bullying behavior in respondents where before the activity the results showed that the level of knowledge of bullying behavior in respondents was more than good as many as 18 people (60%), 12 people (40%) had sufficient knowledge of bullying behavior about bullying behavior. The level of knowledge of bullying behavior after being given health education 30 people (100%) the majority have knowledge of bullying behavior.